Growth performance and blood profile of gestating wad ewes fed dietary supplementation of ammonium sulphate (2016)
The concern raised as a result of antibiotic usage in the livestock industry has necessitated the need for alternative feed additives such as ammonium sulphate. Hence, sixteen West African Dwarf (WAD) ewes averaging 24 kg in weight and aged eighteen months were used to determine the growth performance and blood chemistry of ammonium sulphate supplemented diets. The animals were divided into four groups of experimented diets consisting: D1 (0 %) (Control diet), D2 (0.25 %), D3 (0.50 %) and D4 (0.75 %) of ammonium sulphate (AMS) inclusion levels and were randomly allotted in a completely randomized design. They were also synchronized with prostaglandin F(2α) and naturally mated with four (4) rams of proven fertility when they came on heat. Parameters determined were feed intake, dry matter intake (DMT), gestating weights and gains, and blood haematology and serum biochemistry such as white blood cells (WBC), red blood cell (RBC), packed cell volume (PCV), haemoglobin (HGB), albumin (A), globulin (G), total protein (TP), cholesterol (CHOP), blood urea nitrogen, creatinine (C), alanine aminotransferase (ALT), aspartate aminotransferase (AST) and alkaline phosphatase (ALP). The results showed that supplementing AMS in ewe diets generally enhanced (p < 0.05) final weight (Kg), gestational weight gain (Kg) and average daily weight gain (g). The values ranged from 32.00-45.25 Kg; 8.25 - 22.25 Kg; 207.79 - 267.86 g/d respectively. The feed conversion ratio improved with increasing levels of AMS with animats on D4 recording the least (0.20). Animals on Dl recorded the highest values for PCV, HGB, and RBC while those on D3 had the least. The values were 44.25 and 41.00 %; 14.68 and 13.40 g/dl; and 13.02 and 11.86 x 10(6)/mm(3) respectively. Animals on D4 recorded the highest values for WBC (5150.50 x 10(6)/mm(3) ). Serum biochemical responses of pregnant sheep indicated significant differences (p < 0.05) of AMS supplementation on TP, A/G ratio, ALP and creatinine values. Animals on Dl recorded the highest values for TP, A/G ratio; ALT, BUN and C white those on D2 were least except jar ALT where D3 was least in ALT. The values were 8.68 and 8.15 g/dl; 0.80 and 0.65; 289 and 235.50 I.U./L; 10.75 and 9.75 mg/dl; 1.48 and 1.08 mg/dl respectively. Animals on D2 recorded the highest values for G, ALP and CHOL (4.80 mg/dl; 25.25 1. U/L; and 63.00 mg/dl respectively). Inclusion of AMS improved conversion ratio thereby improving the performance of ewes and thus proved that it could be tolerated up to 0.75 % supplementation in diets for ewes.